Pengaruh Work Environment, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja UMKM Kabupaten Demak - Mutrofin Rohmaniah; Rauly Sijabat; Rita Meiriyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to test and determine the effect of work environment, work motivation, and work discipline on the performance of MSMEs in Demak Regency. This study uses a quantitative method. The population in this study, the author uses the population of MSME actors in Dempet District, Demak Regency in the culinary, fashion, automotive, and agribusiness sectors, totaling 282 MSMEs. Based on the sample calculation using the Slovin formula, it can be seen that the sample in this study is 165 MSMEs. The sampling technique used in this study is the probability sampling method, all elements (eg: people, households) in a population have an equal opportunity to be selected in the sample. The results of this study are that the work environment affects performance, work motivation affects performance, and work discipline affects the performance of MSMEs in Demak Regency.